Epidemiology of urticaria in German children. (3rd May 2021) - Staubach, Petra; Mann, Caroline; Peveling‐ Oberhag, Adriane; Lang, Berenice M.; Augustin, Matthias; Hagenström, Kristina; Garbe, Claudia; Petersen, Jana
Summary: Background: To date, robust epidemiological metrics as well as data on comorbidity in pediatric urticaria are lacking. They form the basis for the design of efficient healthcare. Methods: Retrospective study to analyze epidemiological data in pediatric urticaria. The analysis is based on routine data of a health insurance company operating throughout Germany (DAK‐Gesundheit). Insured people under 18 years of age who received at least one confirmed outpatient or inpatient urticaria diagnosis according to the ICD‐10 classification in the years 2010 to 2015 were included in the analysis and compared to children without a corresponding diagnosis. Results: Of 2.3 million insured individuals, 313, 581 (13.5 %) were under 18 years of age (153, 214 female). Urticaria was diagnosed in 1.7 % of the 313, 581 patients. The prevalence of urticaria decreased with age from 3.0 % in the 0–3‐year age group to 1.0 % in the 14–18‐year age group. Boys and girls were almost equally affected in all age groups. Atopic diseases as comorbidity occurred more frequently in children with urticaria than in the control group (16.0 % vs. 8.0 %). Autoimmune diseases, mental health problems, and obesity also occurred more frequently in children with urticaria than in the control group. Conclusions: The increased prevalence of specific comorbidities in children with urticaria suggests an increased need for screening. Multimodal treatment strategies need to be developed and interdisciplinary collaboration promoted.